Assessment of depression and predictors among obese and non-obese adults: a cross-sectional comparative study - Sirwan Khalid Ahmed; Faisal Mustafa Braim; Kochr Ali Mahmood (Middle East Current Psychiatry)
Abstract Background Obesity and depression are global common, interrelated public health diseases with rising incidences in low- and middle-income countries. With as much evidence as has confirmed the bidirectional association between obesity and depressive disorders, data from Middle Eastern groups like Iraq are lacking. The objectives of this study were to compare and evaluate the severity of depression among obese and non-obese adults residing in the Kurdistan Region of Iraq and to identify the sociodemographic predictors of the severity of depression. Methods Cross-sectional comparative study was conducted among 300 adults (150 obese and 150 non-obese), who were sampled from Rania City outpatient clinics and primary healthcare centers during November 2024 and April 2025. Depression was assessed using the Kurdish translated 9-item Patient Health Questionnaire (PHQ-9), which had been validated. Ordinal regression analysis was employed to examine predictors of depression severity. Results Depressive symptoms were significantly higher in obese individuals compared to non-obese individuals. Passive suicidal ideation and feelings of worthlessness were significantly more common in the obese group. Obesity was an independent predictor of depression (OR = 2.62; 95% CI 1.66–4.14; p < 0.001), whereas age, gender, education level, and smoking status were not statistically significant predictors. Conclusion Severe depression is strongly correlated with obesity in this Iraqi adult population. These results confirm the requirement for combined models of care in managing obesity and psychiatric conditions. Mental health screening should routinely be performed in obese people, particularly in multicultural and deprived environments.